(untitled) (The Review of Diabetic Studies, 2025)
Background: Lumbar disc herniation (LDH) is a leading cause of lower back pain and functional impairment, often requiring surgical intervention when conservative management fails. The evolution of minimally invasive surgery (MIS) aims to reduce perioperative morbidity while maintaining outcomes comparable to open procedures. Objective: To systematically review and synthesize evidence comparing MIS and open surgical approaches for lumbar disc herniation and degenerative lumbar disease, focusing on perioperative outcomes, functional recovery, complications, and long-term stability. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Electronic searches of PubMed, Scopus, Web of Science, Embase, and Google Scholar were performed through December 2025. Eligible studies included randomized controlled trials, prospective and retrospective cohorts, and controlled observational studies comparing MIS and open lumbar surgery. Data extraction and quality assessment were performed independently by two reviewers, with discrepancies resolved by a third reviewer. Results: Eleven studies met inclusion criteria, including MIS-TLIF, microendoscopic discectomy (MED), and percutaneous endoscopic lumbar discectomy (PELD) compared with open TLIF or open discectomy. MIS consistently demonstrated reduced intraoperative blood loss, shorter hospital stay, and faster early functional recovery (Khan et al., 2024; Hartmann et al., 2022; Virdee et al., 2017). Long-term functional outcomes and fusion rates were comparable between groups (Tsertsvadze et al., 2025; Perez-Cruet et al., 2014; Österman et al., 2006). Early learning curve–related complications were reported but decreased with surgical experience and technological advances (Villavicencio et al., 2010; Wang et al., 2025). Conclusion: MIS offers superior perioperative outcomes and faster early recovery without compromising long-term functional results or fusion rates, supporting its preferential use in appropriately selected patients.